The Volatility Costs of Procyclical Lending Standards : An Assessment Using a Dsge Model - Sgherri, Silvia (IMF Working Papers; Working Paper, 2009)
The ongoing financial turmoil has triggered a lively debate on ways of containing systemic risk and lessening the likelihood of boom-and-bust episodes in credit markets. Particularly, it has been argued that banking regulation might attenuate procyclicality in lending standards by affecting the behavior of banks' capital buffers. This paper uses a two-country DSGE model with financial frictions to illustrate how procyclicality in borrowing limits reinforces the 'overreaction' of asset prices to shocks described by Aiyagari and Gertler (1999), and to quantify the stabilization gains from policies aimed at smoothing cyclical swings in credit conditions. Results suggest that, in financially constrained economies, the ensuing volatility reduction in equity prices, investment, and external imbalances would be sizable. In the presence of cross-border spillovers, gains would be even higher.